Analysis of the Student Ability of Understanding Mathematics in Mathematical Statistics I - Suwarman, Ramdhan F (xxxx-xxxx)
A good understanding of the concept of science that is being studied will deliver students to a higher cognitive level. Therefore, it is necessary to do research on understanding the concept of students in a science that is being studied. The research method will be carried out using a quantitative descriptive method with research subjects of third-level students in the subject of Mathematical Statistics I, Mathematics Education Study Program Suryakancana University Academic Year 2016-2017. Data collection techniques are carried out using a test instrument. Results in this study 1) In general, students have good mathematical understanding skills in Mathematical Statistics I. Course 2) Most students still have difficulty in solving problems related to the prerequisite material, in this case about infinite geometry series, the use of properties logarithmic properties, and integration techniques or differentiation. 3) The most common mistake that occurs in the settlement made by students is algebraic operations. It is expected that after this research there will be improvements, both in the form of curriculum improvement, teaching methods, or teaching materials